Performing COVID-19 Control in Finland: Interpretative Topic Modelling and Discourse Theoretical Reading of the Government Communication and Hashtag Landscape - Koljonen, Juha; Palonen, Emilia (Frontiers in Political Science, 2021)
This article discusses discursive transformations in the performance of the government and the “hashtag landscape,” studying Twitter discussions and the female-led government of one of the youngest Prime Ministers in the world, Sanna Marin of Finland. Among the countries in Europe, Finland has been, in the period of analysis of March 2020 to January 2021, one of the least affected countries by the COVID-19 pandemic. Our datasets from both Twitter discussions and the government’s press conferences in 2020 reveal which were the emerging topics of the pandemic year in Finland and how they were discussed. We observe a move from consensual governmental political control to control in the hands of the authorities and ministers responsible, performing a different basis for the pandemic. On the “hashtag landscape,” facemasks continually emerge as an object of debate, and they also become a point of trust and distrust that the government cannot ignore. In terms of comparative governance, this article also notes how the emergency powers legislation shifted control to the government from regional authorities and municipalities in spring 2020, and by that autumn, those powers were returned to regional and local bodies. We recognize several themes that were contested and the discursive field’s transformations and interplay with the authorities.